(3GdeSDhdjI GdGLJeGYjI defXeGJ GdCYeGd s (3ebGQHI dJMbjb GdejRI GdJfGaSjI s - (3bGTj(B, (3NGdOs; (3HhOjSI, CMeOs ((3GdLRGFQ s (3OGQ CLjGd GdQbej s, 2023)
(3jJfGhd GdcJGH GdJCUjd GdfXQj ddeSDhdjI GdGLJeGYjI ddeDSSGJ HeG ajgG Gdeaghe hGdJWhQ GdJGQjNj hGdCgejI, GdejRI GdJfGaSjI JMOj GdeDSSGJ GdeYGUQI h JMdjd JCKjQ CHYGO GdeSDhdjI GdGLJeGYjI ddeDSSGJ Ydi JMbjb GdejRI GdJfGaSjI eY PcQ feGPL Yf eDSSGJ YGdejI JWHb GdeSDhdjI GdGLJeGYjI(B. s
Keywords: (3EOGQI GdCYeGds; (3GdGSJQGJjLjI GdJfGaSjIs; (3GdeSDhdjI GdGLJeGYjIs